2010
DOI: 10.1021/om100400b
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Ethylene Tetramerization Catalysts Derived from Chiral DPPDME Ligands: Syntheses, Structural Characterizations, and Catalytic Performance of [(DPPDME)CrCl3]2 (DPPDME = S,S- and R,R-chiraphos and meso-achiraphos)

Abstract: Chromium-based ethylene tetramerization catalyst precursors of the type {(DPPME)CrCl 2 ( μ-Cl)} 2 with a chiraphos ligand backbone [DPPME = {Ar(R 1 R 2 )} 2 PCH(CH 3 )CH(CH 3 )P{Ar(R 1 R 2 )} 2 ] were prepared and characterized, in which substituents on the aryl phosphine varied with electron-donating and -withdrawing groups (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Improved catalyst activity resulting from increased steric bulk and steric interactions is also demonstrated by dramatic increases in catalytic activity of diphosphine ligands with one or two carbon linkers. However, too much ligand steric bulk could impede ethylene coordination to the catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved catalyst activity resulting from increased steric bulk and steric interactions is also demonstrated by dramatic increases in catalytic activity of diphosphine ligands with one or two carbon linkers. However, too much ligand steric bulk could impede ethylene coordination to the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Information on Vbur and G‐parameters of Cr‐ligand complexes as pre‐catalysts for ethylene oligomerisation can be obtained from crystallographic data . All the available data confirm the tendency to firstly increase and then reduce 1‐octene selectivity with increasing steric bulk.…”
Section: Introductionmentioning
confidence: 85%
“…Cheong employed Cr complexes with stereoisomers of 1,2-dimethyl-1,2-bis(diarylphosphino)ethane ligands and obtained catalytic activity of 274-2,256 kg (g Cr) -1 h -1 for ethylene tetramerization [135]. The racemo-(S,S) or (R,R) complexes show higher activity and 1-octene selectivity than meso-(S,R) complex.…”
Section: Effect Of Ligand Structurementioning
confidence: 99%
“…The results of the temperature study reveal considerable changes in the product distribution with temperature variation, showing an increasing trend in selectivity to 1-hexene and a decreasing trend in selectivity to 1-octene with increasing reaction temperature. In terms of the reaction mechanism [21], it can be concluded that at higher temperatures, the reductive elimination of 1-hexene is favored over -hydride transfer to chromium. Noteworthy by-products of this reaction include methylcyclopentane and methylenecyclopentane (at an almost 1 : 1 ratio).…”
Section: The Effect Of Reaction Temperature On Catalytic Propertiesmentioning
confidence: 99%